Denial : why business leaders fail to look facts in the face--and what to do about it - Tedlow, Richard S. (Portfolio, 2010)
The Harvard Business School professor and author reveals the sources and consequences of denial in business, citing numerous examples from top organizations while identifying leadership skills for recognizing and countering harmful denial behaviors.